2017
DOI: 10.1177/0042098016686511
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low-income households, housing affordability and the Great Recession

Abstract: The effects of the Great Recession on housing equity and homeownership have been well-documented. However, we know little about how rental households fared and the efficacy of housing subsidies in addressing affordability gaps. This paper examines the extent to which rental housing became less affordable for Extremely Low-Income (ELI) households – those earning less than 30% of the Area Median Income (AMI). I then run regression models to determine the local characteristics most strongly associated with larger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 24 publications
0
14
0
1
Order By: Relevance
“…Indeed, in both Manhattan and Brooklyn, new lease signings continued to fall through June 2020 and the vacancy rate of rental units climbed to levels not seen in over a decade ( Haag, 2020 ). However, past work has shown that rental market indicators like listing volume, vacancy rates, and rental price remain relatively sticky during economic downturns and do not necessarily covary ( Genesove, 2003 ; Lens, 2018 ; also see Gabriel & Nothaft, 2001 ).…”
Section: External Shocks To the Housing Marketmentioning
confidence: 99%
“…Indeed, in both Manhattan and Brooklyn, new lease signings continued to fall through June 2020 and the vacancy rate of rental units climbed to levels not seen in over a decade ( Haag, 2020 ). However, past work has shown that rental market indicators like listing volume, vacancy rates, and rental price remain relatively sticky during economic downturns and do not necessarily covary ( Genesove, 2003 ; Lens, 2018 ; also see Gabriel & Nothaft, 2001 ).…”
Section: External Shocks To the Housing Marketmentioning
confidence: 99%
“…Moreover, some scholars have illustrated an acute housing affordability crisis in the South, especially in Florida that has been attracting young as well as retired/senior residents due to its warmer climate and tax‐friendly policies 5 . Other hotspots of decreasing affordability include the metropolitan statistical areas (MSAs) of Houston, Atlanta, and Baton Rouge (Lens, 2018).…”
Section: Theoretical Background and Empirical Progressmentioning
confidence: 99%
“…Indeed, rent burden has become more widespread across the U.S. and its magnitude has been increasing since the Great Recession (ibid). Other scholars have also acknowledged and analyzed the aggravation of rent burden since the recession (Dawkins & Jeon, 2018 ; Edmiston, 2016 ; Lens, 2018 ), and in 2015, almost a half of U.S. tenants paid more than 30% of their income on rent (Gabriel & Painter, 2020 ). Thus, studying the issue of rent burden is crucial, especially holistically and from a geographic perspective across diverse settings, not only within the American context, but also across the world.…”
Section: Rent Burden Its Determinants and Consequencesmentioning
confidence: 99%
“…American scholars have examined rent burden among renters in low-income housing tax credit (LIHTC) units (O’Regan & Horn, 2013 ; Williamson, 2011 ), participants in the housing choice voucher program, HCVP (Dawkins & Jeon, 2018 ; Mast, 2014 ; McClure, 2005 ), or both (Lens, 2018 ). For example, O’Regan and Horn ( 2013 ) considered LIHTC renters in 18 states and concluded that the program helped its tenants to reduce rent burden relative to people with comparable incomes.…”
Section: Rent Burden Its Determinants and Consequencesmentioning
confidence: 99%